The Role of Supporting Examinations on the Diagnosis of Chronic Diarrhea in Children - Deddy S Putra; Muzal Kadim; Pramita G D; Badriul Hegar; Aswitha Boediharso; Agus Firmansyah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Background: Etiology of chronic diarrhea can be established through non-invasive examination such as stool examination and stool culture. Colonoscopy is an invasive Method, which is occasionally needed to discover the etiology of chronic diarrhea. Objective: To recognize the characteristics of chronic diarrhea based on stool examination and colonoscopy results. Methods: Descriptive study on patients with chronic diarrhea who came to Cipto Mangunkusumo hospital since 1 June to 31 August 2005. Laboratory tests were conducted in accordance with clinical indication. Data was presented in distribution tables. Results: There were 41 patients with chronic diarrhea. Stool examination were performed only in 38 patients with negative-gram infection (86.8%). Stool cultures were performed in 27 patients with positive results of non-pathogenic Escherichia coli (85.2%). Stool parasite examination and concentration tests were performed in 17 patients, with 47.0% positive results as follow: Microsporidia 29.4%, Blastocystis hominis 11.8% and Giardia lamblia 5.9%. Colonoscopy examinations were performed in 6 patients and all patients indicated ulcerative colitis appearance with 50% histopathological impression of infective colitis. Conclusion: Stool examination in chronic diarrhea primarily indicates positive infection. Bacterial stool culture mostly includes non-pathogenic Escherichia coli, while parasite stool examination largely includes Microsporidia. Biopsy examination tends to reveal infective colitis. Keywords: chronic diarrhea, parasite stool, colonoscopy